REASONING AS ENGAGEMENT IN FAITHS - Adian, Donny Gahral (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2009)
Beliefs are founded upon the ultimate being as an ultimate cause or principle. Some claim that the ultimate being, God, emanates itself into many, other claims that God created the world out of nothing. Whatever one believes in, one thing is clear : the ultimate being reveals itself in a spatio-temporal world; in a heterogeneous and not in a homogeneous world. The consequence is : revelation is not only one. There are many different communities with their respective faiths. However, many are not aware of the contingency of their faith. They are trapped into absolutism and try to mold the world into the emporium of their true faith. Blinded by their isolated faith, some use any means necessary, including violence, to attain the highest ideal. The reasoning behind such attitude is the instrumental form of reasoning combined with a high dose of encapsulated faith. This article explores the relation between faith, way of life, values and what kind of reasoning is appropriate in a world of multiple faiths.